Singular limit solutions for a 2-dimensional semilinear elliptic system of Liouville type in some general case adding singular sources (Part II). (July 2020) - Baraket, Sami; Bazarbacha, Imen; Chetouane, Rima
Abstract: We consider the existence of singular limit solutions for a nonlinear elliptic system of Liouville type with singular sources terms given by Dirac masses and Dirichlet boundary conditions. We use the nonlinear domain decomposition method and the Pohozaev identity.